Development Analysis Of Pematangsiantar Urban Forest - Nurrachmania, Meylida (Universitas Andi Djemma Palopo, 2025)
Pematangsiantar City is a strategic city because it connects the east coast and west coast of North Sumatra Province and is a gateway city to the Lake Toba tourist area. The purpose of this study was to analyze the development of the Pematangsiantar urban forest. Data were analyzed descriptively and qualitatively with the SWOT method. The internal strength factor is 0.102 which is found in three aspects of strength, namely clarity of status, high accessibility and quite strategic on the main road to the urban forest, and government policy support in urban forest development. Meanwhile, the green space area as a place for people to gather received a weight of 0.061. So from the calculation of weight and rating, it is obtained that the strength aspect of government policy support in forest development gets the highest score of 0.466. As for the weaknesses in the urban forest development strategy, namely the lack of promotion and marketing of urban forests, there has been no sufficiently in-depth research on urban forests, low public awareness to preserve urban forests, and the condition of the urban forest area is classified as less clean and well-maintained getting the highest weight of 0.102, while the aspect of the lack of facilities and infrastructure for visitors gets the lowest weight value of 0.061.